Adenosquamous carcinoma of the pancreas with an acantholytic pattern together with osteoclast-like and pleomorphic giant cells. Issue 9 (26th August 2005) - Alwaheeb, S; Chetty, R
Abstract : A 45 year old man presented with abdominal pain, loss of appetite, and significant weight loss over a period of about four weeks. Imaging of the abdomen showed a mass in the region of the head of the pancreas. In view of the size of the mass and the clinical picture, a Whipple's procedure was performed. Histological evaluation of the pancreatic tumour showed an adenosquamous carcinoma (predominantly composed of squamous carcinoma), which was extensively infiltrative with perineural invasion and involvement of peripancreatic lymph nodes. Areas of pancreatic intraepithelial neoplasia grade III and merging of the squamous and adenocarcinoma components were evident. Unusual histological features that characterised this case included a pronounced acantholytic pattern within the squamous carcinoma component, and the presence of both osteoclastic and pleomorphic giant cells. Giant cells have not been documented previously in association with an adenosquamous carcinoma. Although an acantholytic pattern has been noted in squamous carcinomas in other sites, this is the first report of such a pattern in an adenosquamous carcinoma of the pancreas.